Kurt Baschwitz : A Pioneer of Communication Studies and Social Psychology - Ginneken, Jaap van, 1943- (Book collections on Project MUSE., 2018)
In this study of a forgotten but noteworthy figure, the author tells the story of the life of Kurt Baschwitz (1886-1968), a scholar who fled from the Nazis. He wrote six books, never translated into English, on four related themes: the press, propaganda, politics, and persecution. Baschwitz independently developed concepts that are now seen as key to communication science and social psychology, and the author places Baschwitz's ideas in the wider context of his dramatic life and times.